Demographic and work-related factors associated with burnout, resilience, and quality of life among healthcare workers during the COVID-19 pandemic: a cross sectional study from Malaysia - Marzo, Roy Rillera; ElSherif, Mohamed; Abdullah, Muhd Siv Azhar Merican; Hui, Zhu Thew; Chong, Collins; Shean, Yih Soh; Ching, Sin Siau; Chauhan, Shekhar; Yulan, Lin (Frontiers Research Foundation, 2022)
Introduction: The healthcare setting is a stressful and demanding work environment, and healthcare workers face a continuous expansion of their job roles and responsibilities. Past studies have shown that factors affecting burnout, resilience, and quality of life among healthcare workers merit further research, as there were inconsistent findings, especially with regards to the influence of demographic and work-related factors. Therefore, this study aims to determine whether demographic and work-related factors are associated with burnout, resilience, and quality of life among healthcare workers.